Flatfish fishery off Cochin and some aspects of the biology and stock of Malabar sole Cynoglossus macrostomus (Norman) - Nair, Rekha J (Indian Journal of Fisheries, 2011)
Flatfish landings increased from an estimated 58 t in 2000 to 299 t in 2002, but declined to 65 t in 2003 and 61 t in 2004 at Cochin. August and September were the months of peak landings, which were also the peak spawning months. The optimum length of exploitation was 124 mm. Annual growth coefficient (K) and Lô€ƒ were 0.79 and 212.5 mm respectively. The resource is being exploited at a level (E = 0.78) higher than the optimum (Emax = 0.458). Appropriate management measures are discussed.